3D‐Printed Hydrogel‐Filled Microneedle Arrays. Issue 13 (29th May 2021) - Barnum, Lindsay; Quint, Jacob; Derakhshandeh, Hossein; Samandari, Mohamadmahdi; Aghabaglou, Fariba; Farzin, Ali; Abbasi, Laleh; Bencherif, Sidi; Memic, Adnan; Mostafalu, Pooria; Tamayol, Ali
Abstract: Microneedle arrays (MNAs) have been used for decades to deliver drugs transdermally and avoid the obstacles of other delivery routes. Hydrogels are another popular method for delivering therapeutics because they provide tunable, controlled release of their encapsulated payload. However, hydrogels are not strong or stiff, and cannot be formed into constructs that penetrate the skin. Accordingly, it has so far been impossible to combine the transdermal delivery route provided by MNAs with the therapeutic encapsulation potential of hydrogels. To address this challenge, a low cost and simple, but robust, strategy employing MNAs is developed. These MNAs are formed from a rigid outer layer, 3D printed onto a conformal backing, and filled with drug‐eluting hydrogels. Microneedles of different lengths are fabricated on a single patch, facilitating the delivery of various agents to different tissue depths. In addition to spatial distribution, temporal release kinetics can be controlled by changing the hydrogel composition or the needles' geometry. As a proof‐of‐concept, MNAs are used for the delivery of vascular endothelial growth factor (VEGF). Application of the rigid, resin‐based outer layer allows the use of hydrogels regardless of their mechanical properties and makes these multicomponent MNAs suitable for a range of drug delivery applications. Abstract : A 3D‐printed, multiheight microneedle array is developed for the delivery of multiple therapeutics to different tissue layers. Multimaterial printing creates needles strong enough to penetrate skin while the array conforms to tissue topography. The stiff resin shell encases a drug‐eluting hydrogel core, which protects loaded biologics. Upon insertion, the varied needle lengths facilitate controlled drug delivery at different depths.